Analisis Pemahaman Guru Terhadap Standar Pendidik Dan Tenaga Kependidikan (PTK) Di Tingkat SMP/MTS - Astuti, Eva Karlina Dwi; Rochman, Chaerul; Farida, Ida; Hasanah, Aan (Tawazun: Jurnal Pendidikan Islam, 2020)
Teachers’ understanding of aspects related to the standards of educators and education personnel is very important to realize quality education. For this reason, through this research, an analysis of the standards of educators and education staff has been carried out in order to achieve the success of an education. This study aims to interpret or illustrate the data accompanied by the achievement of an understanding of the standard of educators and education staff on PAI Teachers and Non PAI Teachers. This research method is quantitative descriptive. The instrument for collecting data uses questionnaires and interviews. Based on the analysis of data on the understanding of PAI Teachers and Non PAI Teachers that there are indicators whose percentage qualification scores are lacking, namely the 2nd and 17th indicators. The comparison of the percentage of PAI and Non-PAI teachers’ understanding of the standards of educators and education personnel is 78.7% and 78.4%. The results of the triangulation of respondents there are three indicators: the 2nd indicator from PAI teachers and the 16th indicators and the 17th indicators from Non-PAI teachers, so there is a need for more attention and improvement by schools to the difficulties faced in the standards of educators and educational. Abstrak Pemahaman guru terhadap aspek-aspek yang terkait dengan standar pendidik dan tenaga pendidikan sangat penting untuk merealisasikan penyelenggaraan pendidikan yang berkualitas. Untuk itu melalui penelitian ini telah dilakukan analisis terhadap pemahaman standar pendidik dan tenaga kependidikan guna mencapai keberhasilan dari suatu pendidikan. Penelitian ini bertujuan untuk melakukan penafsiran atau menggambarkan data disertai dengan ketercapaian pemahaman standar pendidik dan tenaga kependidikan pada Guru PAI dan Guru Non PAI. Metode penelitian ini adalah kuantitatif deskriptif. Instrumen untuk mengumpulkan data menggunakan angket dan wawancara. Berdasarkan hasil analisis data pemahaman Guru PAI dan Guru Non PAI bahwa terdapat indikator yang nilai kualifikasi prosentasenya kurang yaitu pada indikator ke-2 dan indikator indikator ke-17. Perbandingan prosentase pemahaman Guru PAI dan Non PAI terhadap standar pendidik dan tenaga kependidikan ialah 78,7 % dan 78, 4 %. Hasil triangulasi responden ada tiga indikator yaitu: indikator ke-2 dari Guru PAI dan indikator ke-16 serta indikator ke-17 dari Guru Non PAI, sehingga perlu adanya perhatian lebih dan perbaikan oleh sekolah terhadap kesulitan yang dihadapi pada standar PTK.